1990
DOI: 10.1159/000186092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Clodronate in Severe Hyperparathyroid Bone Disease in Chronic Renal Failure

Abstract: We have examined the effects of the diphosphonate, clodronate, in 9 haemodialysis patients with severe hyperparathyroid bone disease. Clodronate (300–600 mg infused after dialysis on 5 consecutive occasions) significantly decreased mean serum calcium, phosphate and hydroxyproline. This was associated with an increase in serum immunoassayable parathyroid hormone and activity of alkaline phosphatase. These changes reversed 2–4 weeks after stopping treatment but were sustained when treatment with oral clodronate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 23 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Clinically, the affinity of bisphosphonates to bone in dialysis patients is related to the degree of HPT, although bisphosphonate effects in patients with CKD‐5D have only been examined in a limited number of studies. Administration of clodronate in nine HD patients with severe HPT produced inhibition of osteoclast‐mediated bone resorption (91) and in a RCT of 31 HD patients, hip BMD remained stable after 6 months in patients treated with alendronate compared to a reduction in those on placebo (92). However, in the latter study this difference was minimal (despite statistical significance) and the treatment time was short.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Clinically, the affinity of bisphosphonates to bone in dialysis patients is related to the degree of HPT, although bisphosphonate effects in patients with CKD‐5D have only been examined in a limited number of studies. Administration of clodronate in nine HD patients with severe HPT produced inhibition of osteoclast‐mediated bone resorption (91) and in a RCT of 31 HD patients, hip BMD remained stable after 6 months in patients treated with alendronate compared to a reduction in those on placebo (92). However, in the latter study this difference was minimal (despite statistical significance) and the treatment time was short.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…In experimental renal failure, ibandronate prevents hyperparathyroid bone changes and increases bone volume [65]. Clodronate given after hemodialysis induces a significant decrease in serum calcium levels and interestingly an increase of parathyroid hormone in hemodialysis patients [66]. Elimination of ibandronate in patients on hemodialysis has been studied and ibandronate was shown to be efficiently removed by hemodialysis.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…They are widely used to treat postmenopausal or glucocorticoid-induced osteoporosis, but little evidence is available on their effectiveness and safety in patients on HD. Previous studies reported that BPs were a potential treatment for renal osteodystrophy, particularly in patients with high bone turnover or hypercalcemia related to increased release of calcium from bone [ 11 , 12 ], and that they may be beneficial in HD patients [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%